GRID anti-theft system - Neer Pandi, Rhuban (2012)
Global System for Mobile Communications(GSM)seems to be the best solution to develop outdoor alerting system, but performance of these systems is not good enough to local entities within indoor environments,mainly if accuracy and precision are required.With the technology of Radio frequency identification (RFID) and GSM, many researches are being carried out on monitoring entities as it does provide accuracy and precision.Plus,the technology is applicable to develop new variation of identification, and anti-theft system.Accordingly,in this project,we propose an anti-theft system combining GSM and RFID technology that is able to accurately monitor and alert various valuable entities.The proposed system can alert the user when the entities moved out of the define parameters and then the system can notify the owner by sending message when the entities moved out of the parameter.